Cultivating conditions influence invertase production by Aspergillus Niger in submerged culture - Mohamad Izhar, Mohd Samin (2012)
Recently,there was increased in the production of microbial invertase due to its function which was important in production of invert sugar and high fructose syrup as compared to production of high fructose syrup and invert sugar for formulation of pharmaceutical product from sucrose by using acid hydrolysis.Therefore this study was conducted to examine the effect of substrate concentration by using sucrose from table sugar as cheaper carbon source of to provide an alternative production without implement other steps to secure the carbon source to be used in microbial invertase production by Aspergillus niger.This study was also conducted to study effect of pH and agitation speed on cultivating conditions by One Factor at a Time (OFAT) and eventually optimize the parameters for invertase production in submerged culture by using central composite design (CCD) in Design Expert for Response Surface Methodology (RSM) in submerged fermentation.The studied parameter were substrate concentration in selected range 10-50% (w/v), pH in range of pH 4.5-6.5, and agitation speed in range of 100-300 rpm. Studied conducted on one factor at a time yield maximum amount of invertase activity at 30 g/L sucrose concentration,pH 5.5 and 250 rpm with amount of 8.9132 IU/mL,8.6754 IU/mL and 8.3429 IU/mL respectively after 40 hours fermentation period. After optimization of these three parameters using Response Surface Methodology (RSM),the optimum cultivating condition was obtained at 26.9583 IU/mL by using 30 g/L of sucrose concentration,pH 5.5 and 200 rpm. The optimum cultivating condition effect on invertase production in submerged culture was concluded at optimum condition obtain at 30 g/L sucrose concentration, pH 5.5 and 200 rpm from the study conducted by using central composite design since it had indicated that these three factors were significant with R2 value of 0.9950 (P<0.001). Based on the result obtained from this study,it was recommended that table sugar can be used as carbon source and the model obtained can be further reviewed to ensure effective invertase production in submerged culture by Aspergillus niger.